Research on Structure Optimization of T-tube oil-water Separator - Wu, Hao (Scientific Journal of Technology, 2026)
The traditional produced liquid is separated from oil and water at the combined station, but the process has large energy consumption, high operating costs, and some of the combined stations are small in treatment scale, which is difficult to adapt to the increasing water content treatment needs. The tubular separator is used to separate the high water content free water in the produced fluid of the well site to achieve "on-site separation and on-site reinjection", which is convenient and efficient. In this paper, the flow field characteristics and separation process of T-shaped pipe are studied by numerical simulation, and the number of branch pipes, horizontal pipe diameter and branch pipe length of T-shaped pipe are optimized on this basis, and the influence of the above structural parameters on the oil-water separation effect is analyzed. The simulation in this paper is carried out under the conditions of inlet mixing flow rate of 0.1m·s-1, oil content of 5%, and split ratio of 0.5, and the main conclusions are as follows: (1) The number of branch pipes has little effect on the velocity distribution law of the oil-water two phases, and both show that in the main pipe, the speed of both phases gradually decreases with the flow direction; in the branch pipe, the speed is the highest; the water phase has a slower velocity in the top area of the main pipe (the aggregation area of the oil phase), and the oil phase has a significantly higher flow rate in this area than the water phase. In manifold pipes, the above velocity distribution trend is more pronounced. (2) The increase of horizontal pipe diameter will lead to a slower speed of the liquid in the pipe, and the slower flow speed will lead to a longer residence time of the liquid in the pipeline, so the separation effect of the oil-water mixture will decrease. The increase of the number of branch pipes and the decrease of horizontal pipe diameter can significantly improve the separation efficiency, while the increase of the length of branch pipes does not significantly improve the separation efficiency. The results of this paper are helpful to optimize the structure of T-type tubular separator in the oil-water separation process and improve the separation efficiency of the equipment.